2020
DOI: 10.1002/mabi.202000358
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Curdlan Poly(γ ‐Glutamic Acid) Nanoassembly for Immune Modulation in Macrophage

Abstract: A nanoformulation composed of curdlan, a linear polysaccharide of 1,3‐β‐linked d‐glucose units, hydrogen bonded to poly(γ ‐glutamic acid) (PGA), was developed to stimulate macrophage. Curdlan/PGA nanoparticles (C‐NP) are formulated by physically blending curdlan (0.2 mg mL−1 in 0.4 m NaOH) with PGA (0.8 mg mL−1). Forster resonance energy transfer (FRET) analysis demonstrates a heterospecies interpolymer complex formed between curdlan and PGA. The 1H‐NMR spectra display significant peak broadening as well as do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…This could be explained by the fact that β-glucans are phagocytosed and processed by monocytes and macrophages found in the intestinal lymphatic tissue, and then transported to different immune organs to prepare immune cells for an antimicrobial and in ammatory response against potential pathogens [37]. In contrast, other in vitro studies where β-glucans from A. faecalis are administrated in not pathologic conditions, these produce an increase in the expression of M1 macrophages that have a pro-in ammatory phenotype with pathogen-killing abilities, upregulating Il-6, Il1-β, TNF-α, MCP-1 expression [21,35]. As in our case, in which we have not detected differences in the concentrations of cytokines in the different uids analyzed between the healthy animals (AGUSAN) and the healthy ones pre-treated (AGUSTO), in a study of ex vivo stimulation of leukocytes from healthy adults who received β-glucans, it was observed that no β-glucans were detected in serum.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that β-glucans are phagocytosed and processed by monocytes and macrophages found in the intestinal lymphatic tissue, and then transported to different immune organs to prepare immune cells for an antimicrobial and in ammatory response against potential pathogens [37]. In contrast, other in vitro studies where β-glucans from A. faecalis are administrated in not pathologic conditions, these produce an increase in the expression of M1 macrophages that have a pro-in ammatory phenotype with pathogen-killing abilities, upregulating Il-6, Il1-β, TNF-α, MCP-1 expression [21,35]. As in our case, in which we have not detected differences in the concentrations of cytokines in the different uids analyzed between the healthy animals (AGUSAN) and the healthy ones pre-treated (AGUSTO), in a study of ex vivo stimulation of leukocytes from healthy adults who received β-glucans, it was observed that no β-glucans were detected in serum.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] Therefore, rapid and accurate blood glucose detection is critical for the monitoring of physical health and diabetes treatments. Some existing glucose detection systems, namely, fluorescence method, [38,39] surface-enhanced Raman scattering method, [40][41][42] chemiluminescence method, [43,44] and electrochemistry, [45][46][47] have been thoroughly exploited, and they show enormous potentials in practical applications. However, due to the complex operation and expensive instrumentation of the electrochemical methods, they have become limited in applications.…”
Section: Introductionmentioning
confidence: 99%